2018
DOI: 10.2174/1570159x15666170830122402
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Gating and Basic Functions of the Ca2+-activated K Channel of Intermediate Conductance

Abstract: BackgroundThe KCa3.1 channel is the intermediate-conductance member of the Ca2+-activated K channel superfamily. It is widely expressed in excitable and non-excitable cells, where it plays a major role in a number of cell functions. This paper aims at illustrating the main structural, biophysical and modulatory properties of the KCa3.1 channel, and providing an account of experimental data on its role in volume regulation and Ca2+ signals.MethodsResearch and online content related to the structure, structure/f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
50
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 82 publications
2
50
0
Order By: Relevance
“…Calmodulin (CaM) gene expression has been shown to be altered in TIL of breast cancer patients (Gu-Trantien et al, 2013). CaM is a signaling molecule that controls multiple T cell functions including KCa3.1 activity which is triggered by an increase in cytosolic Ca 2+ (Cahalan and Chandy, 2009;Sforna et al, 2018). CaM binds to the C-terminus of KCa3.1 and acts as a calcium sensor (Schumacher et al, 2001;Stocker, 2004;Adelman, 2016;Lee and Mackinnon, 2018;Sforna et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Calmodulin (CaM) gene expression has been shown to be altered in TIL of breast cancer patients (Gu-Trantien et al, 2013). CaM is a signaling molecule that controls multiple T cell functions including KCa3.1 activity which is triggered by an increase in cytosolic Ca 2+ (Cahalan and Chandy, 2009;Sforna et al, 2018). CaM binds to the C-terminus of KCa3.1 and acts as a calcium sensor (Schumacher et al, 2001;Stocker, 2004;Adelman, 2016;Lee and Mackinnon, 2018;Sforna et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…CaM is a signaling molecule that controls multiple T cell functions including KCa3.1 activity which is triggered by an increase in cytosolic Ca 2+ (Cahalan and Chandy, 2009;Sforna et al, 2018). CaM binds to the C-terminus of KCa3.1 and acts as a calcium sensor (Schumacher et al, 2001;Stocker, 2004;Adelman, 2016;Lee and Mackinnon, 2018;Sforna et al, 2018). CaM is constitutively bound to the channel in a Ca 2+ -independent manner (Schumacher et al, 2001;Stocker, 2004;Adelman, 2016;Lee and Mackinnon, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compelling evidence shows that mechanical stimulation is an important factor regulating MSC functions, including proliferation, but the underlying mechanism is far from understood . K Ca 3.1 channel, also known as KCNN4, IK Ca and SK4, is an intermediate‐conductance member of the Ca 2+ ‐activated K + channel family and is widely expressed in both excitable and non‐excitable cells, where it plays an important role in various cell functions . Interestingly, there is increasing evidence to support the K Ca 3.1 channel is engaged in MSC proliferation .…”
Section: Introductionmentioning
confidence: 99%
“…and non-excitable cells, where it plays an important role in various cell functions. 8 Interestingly, there is increasing evidence to support the K Ca 3.1 channel is engaged in MSC proliferation. [9][10][11] Previous studies showed that the expression of the K Ca 3.1 channel in human umbilical vein endothelium cells was up-regulated by fluid flow-induced shear stress, or its channel activity in vascular smooth muscle cells was enhanced by hypotonic solution-induced membrane stretch.…”
mentioning
confidence: 99%